Determinants of Professional’s Bank Choice: Empirical Evidence from Bangladesh - Rahman, Md. Bazlur; Chowdhury, Newma (International Business Education Journal, 2022)
Abstract The banking industry has become one of the most competitive service industries in the world during the last two decades where the Bangladeshi banking sector is not exceptional. This competitive environment in the sector forces the commercial banks in Bangladesh to upgrade their service quality and stay updated with new technologies for their growth. Also, it is essential to examine the critical factors in selecting banks to attract bank customers. The professional group of customers, the largest group of personal account holders, represents an attractive segment for commercial banks in Bangladesh. This study aimed to investigate the determinants of the choice of commercial banks by professionals in Bangladesh. The primary data was collected from 395 professionals of bank customers through a structure questionnaire containing eight possible factors that determine customer’s bank choice. Among the eight factors examined, security, advanced technology, convenience, speed, and quality of services are the essential factors that professionals consider when choosing their bank services. The study results have important implications for bank management, academicians, and policymakers to devote resources, evaluate and redesign current marketing strategies to attract the professional group of customers in the competitive bank environment. Keywords: Professional customer, bank selection, bank customer, bank services.